The influence of reaction temperature on the chemical structure and surface concentration of active nox in h2-scr over pt/mgo{single bond}ceo2: ssitka-drifts and transient mass spectrometry studies - Efstathiou, Angelos M.; Savva, Petros G. (My University, 2008)
Steady-state isotopic transient kinetic analysis (SSITKA), transient isothermal, and temperature-programmed surface reaction in H2 (H2-TPSR) techniques coupled with online mass spectroscopy (MS) and in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) were used to study essential mechanistic and kinetic aspects of the selective catalytic reduction (SCR) of NO with the use of H2 under strongly oxidizing conditions (H2-SCR) over a novel Pt/MgO{single bond}CeO2 catalyst. The main focus was to study and report for the first time the effects of reaction temperature on the chemical structure and surface concentration of the active NOx intermediate species thereby formed. The information obtained is essential to understanding the volcano-type profile of the catalyst activity versus reaction temperature observed here and also reported previously. In the present work, two active NOx intermediate species identified by SSITKA-DRIFTS were found in the nitrogen-reaction path toward N2 and N2O formation, one species located in the vicinity of the Pt{single bond}CeO2 support interface region (nitrosyl [NO+] coadsorbed with a nitrate [NO-3] species on an adjacent Ce4+{single bond}O2- site pair) and the second located in the vicinity of the Pt{single bond}MgO support interface region. The chemical structure of the second kind of active NOx species was found to depend on reaction temperature. In particular, the chemical structure was that of bidentate or monodentate nitrate (NO-3) at T < 200 ° C and that of chelating nitrite (NO-2) at T > 200 ° C. The concentration of the active NOx intermediates that lead to N2 formation was found to be practically independent of reaction temperature (120-300 °C) and significantly larger than 1 equivalent monolayer of surface Pt (θNOx = 2.4 - 2.6). The former result cannot be used to explain the volcano-type behavior of the catalytic activity versus the reaction temperature observed; alternative explanations are explored. The H-spillover process involved in the H2-SCR mechanism was found to be limited within a support region of about a 4-5 Å radius around the Pt nanoparticles (dPt = 1.2 - 1.5 nm).
Keywords: Addition reactions; Isotopes; Surfaces